1988 IEEE 5th International Symposium on Spread Spectrum Techniques and Applications - Proceedings. Spread Technology to Africa
DOI: 10.1109/isssta.1998.722531
|View full text |Cite
|
Sign up to set email alerts
|

Hough detector with adaptive non-coherent integration for target detection in pulse jamming

Abstract: It is shown that the Hough transform with binary integration of the data in parameter space may be used for improvement of target detection in the presence of strong Pulse Jamming (PJ). The algorithm proposed may be used for effective detection of small airborne targets whose trajectories are straight radial lines. The expressions for detection probability evaluation are derived for a target model according to the Swerling case U. The expressions obtained are applied to the typical surveillance radar. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…In such a detector, target detection is declared if the signal sample x 0 exceeds a preliminary determined adaptive threshold H D . In case of Poisson and binominal distribution of impulse interference, the analytical expressions for calculating the detection and false alarm probability are obtained in [3,4,[15][16][17].…”
Section: Cfar Processormentioning
confidence: 99%
See 3 more Smart Citations
“…In such a detector, target detection is declared if the signal sample x 0 exceeds a preliminary determined adaptive threshold H D . In case of Poisson and binominal distribution of impulse interference, the analytical expressions for calculating the detection and false alarm probability are obtained in [3,4,[15][16][17].…”
Section: Cfar Processormentioning
confidence: 99%
“…The centralized Hough detector is compared to decentralized Hough detector by detection probability for different binary rules in Hough parameter space; the results are shown on Figure 5. In order to analyze the quality of the Hough detectors we consider radars with equal parameters, similar to those in [2,[9][10][11][15][16][17]. The results have shown that the detection probability of centralized detector is almost twice as much than distributed detector.…”
Section: Comparative Analysis Of the Researched Hough Detectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the standard Hough transform (SHT) for target detection and track determination in white Gaussian noise is introduced by Carlson in [1]. An approach for constant false alarm rate (CFAR) detection by means of SHT for track and target detection in conditions of non-homogeneous background is considered by Behar in [2,3,4]. The Hough detection scheme includes a CFAR signal detector in the area of observation, HT of the target distance measurements from the observation area into the parameter space, binary integration of data in the parameter space and linear trajectory detection.…”
Section: Introductionmentioning
confidence: 99%